A preliminary study on propylene oxidation with oxygen on alumina - Escorial, Ninaliza H. (Animo Repository, 1996)
Propylene oxidation with oxygen on alumina is conducted using a fixed bed flow reactor system equipped with a locally fabricated gas chromatography apparatus. The effects of temperature, partial pressures of the reactants, and the carbon deposited on the surface of the catalyst on the conversion of propylene and yields of carbon monoxide and carbon dioxide are studied. Propylene conversion as well as the yields of carbon monoxide and carbon dioxide from the oxidation of propylene increased as the temperature increased. However, at lower temperature carbon deposits were formed on the surface of the catalyst. At lower temperature, two reactions occurred: oxidation and the formation of carbon deposits. Carbon deposition was optimum at the temperature range of 500 to 650 degree Centigrade. While oxidation was dominant at the temperature of 650 to 750 degree Centigrade. The conversion of propylene at the temperature of 600 degrees Centigrade increased with increasing propylene partial pressure while the yields of both carbon monoxide and carbon dioxide decreased as the partial pressure of propylene increased. At the same temperature, the partial pressure of oxygen did not have effect on the propylene conversion. Propylene conversion and the yields of carbon monoxide and carbon dioxide from propylene oxidation increased with increasing residence time. From the results of the study, it is very evident that modifications should be made on the alumina catalyst to inhibit the formation of carbon deposits on the surface of the catalyst and make it an effective oxidation catalyst. From the results of this study, it is very evident that modifications should be made on the alumina catalyst to inhibit the formation of carbon deposits on the surface of the catalyst and make it an effective oxidation catalyst.